2021
DOI: 10.1093/gerona/glab019
|View full text |Cite
|
Sign up to set email alerts
|

Daily Consumption of a Specially Formulated Essential Amino Acid-Based Dietary Supplement Improves Physical Performance in Older Adults With Low Physical Functioning

Abstract: We have investigated the hypothesis that nutritional supplementation of the diet in low-physical-functioning (LPF) older individuals with a specially formulated composition based on essential amino acids (EAAs) would improve physical function as compared to supplementation with the same amount of whey protein. A third group of comparable volunteers were given nutrition education but no supplementation of the diet.After 6 weeks of whey protein supplementation (n=32) there was no effect on the distance walked in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Therefore, the optimal formulation of an EAA composition to stimulate MPS will have disproportionately greater amounts of leucine and lysine as compared to their respective contributions to the composition of muscle protein. In line with this notion, it was shown that a specially formulated composition of all the EAAs containing approximately 35% leucine and 15% lysine (which exceeds their contributions to the composition of muscle protein) effectively overcame anabolic resistance and stimulated MPS [9,20] and improved functional performance in older adults [5].…”
Section: Role Of Eaas In Stimulation Of Mpsmentioning
confidence: 84%
See 4 more Smart Citations
“…Therefore, the optimal formulation of an EAA composition to stimulate MPS will have disproportionately greater amounts of leucine and lysine as compared to their respective contributions to the composition of muscle protein. In line with this notion, it was shown that a specially formulated composition of all the EAAs containing approximately 35% leucine and 15% lysine (which exceeds their contributions to the composition of muscle protein) effectively overcame anabolic resistance and stimulated MPS [9,20] and improved functional performance in older adults [5].…”
Section: Role Of Eaas In Stimulation Of Mpsmentioning
confidence: 84%
“…It was therefore thought that mimicking the EAA profile in muscle protein would be the most effective composition to stimulate muscle protein synthesis. However, clinical research discovered that the optimal composition of EAAs is different from the EAA profile of muscle protein for several reasons [5,31,36,37]. First, leucine is oxidized in muscle in addition to being incorporated into muscle protein by MPS.…”
Section: Role Of Eaas In Stimulation Of Mpsmentioning
confidence: 99%
See 3 more Smart Citations